Prevalence of overweight/obesity and its associated factors among secondary school students in Batang Padang District, Perak - Alagappan, Mahaletchumy; Gyanchand Rampal, Lekhraj Rampal; Mohd Sharif, Zalilah; Thevandran, Kalaiselvam (Malaysian Medical Association, 2015)
Introduction: Overweight and obese adolescents are at increased risk of significant health problems such as hypertension, diabetes, heart disease, stroke and cancer. The objective of this study is to determine the prevalence and predictors of overweight and obesity among secondary school students.